Effect of pre-sowing treatments on germination and growth of seedlings of calamus spp. - Jisha E D (Department of Forest Management and Utilisation, College of Forestry, 2010)
The present study entitled “Effect of pre-sowing treatments on germination and growth of seedlings of Calamus spp.” was carried out on four Calamus species namely, Calamus thwaitesii, C. metzianus, C. hookerianus, and C. travancoricus in the tree nursery of College of Forestry, Vellanikkara, during 2007 – 2009.